2007
DOI: 10.1007/s10493-007-9109-7
|View full text |Cite
|
Sign up to set email alerts
|

Biological control of twospotted spider mite, Tetranychus urticae, with predatory mite, Neoseiulus californicus, in strawberries

Abstract: Greenhouse and field experiments were conducted from 2005 to 2007 to determine the effectiveness of different release times with the predatory mite, Neoseiulus californicus (McGregor), for control of the twospotted spider mite (TSSM), Tetranychus urticae Koch, in strawberries (Fragaria x ananassa Duchesne). The effect of N. californicus releases over time and on development of TSSM populations during a growing season were evaluated. Our hypothesis was that repeated applications of N. californicus, which is cur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
53
0
6

Year Published

2009
2009
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 65 publications
(63 citation statements)
references
References 25 publications
4
53
0
6
Order By: Relevance
“…The main form of control for T. urticae is the use of synthetic pesticides, together with biological control involving the generalist mite Neoseiulus californicus McGregor, which is a natural predator of T. urticae found in different regions of Brazil (Fraulo and Liburd, 2007). However, the continual use of conventional acaricides has caused serious damage due to environmental contamination as well as the elimination of N. californicus and various pollinating insects (Motazedian et al, 2012).…”
Section: Introductionmentioning
confidence: 99%
“…The main form of control for T. urticae is the use of synthetic pesticides, together with biological control involving the generalist mite Neoseiulus californicus McGregor, which is a natural predator of T. urticae found in different regions of Brazil (Fraulo and Liburd, 2007). However, the continual use of conventional acaricides has caused serious damage due to environmental contamination as well as the elimination of N. californicus and various pollinating insects (Motazedian et al, 2012).…”
Section: Introductionmentioning
confidence: 99%
“…Phytoseiidae is the most important family of acarine predators used in pest management programs (Gerson and Weintraub, 2007;Hoy, 2011). Phytoseiulus persimilis Athias-Henriot and Neoseiulus californicus (MacGregor) are among the species most used in horticultural and greenhouse crops, having been employed in strawberries for TSSM control (Fraulo and Liburd, 2007;Palevsky et al, 2008). Amblyseius swirskii (Athias-Henriot) is a Mediterranean phytoseiid species considered as a primary predator of thrips and whiteflies; it has been recommended and used to control TSSM as well as other pests in greenhouse and strawberry crops (Elsawi and Alazzazy, 2007;Gerson and Weintraub, 2007;Alvarado, 2009;Xu and Enkegaard, 2010;SĂĄenz-de CabezĂłn et al, 2010;Calvo et al, 2011;Kutuk et al, 2011).…”
Section: Introductionmentioning
confidence: 99%
“…50 T. urticae/leaflet [28]. It has also been observed that N. californicus, when released at ratios of up to 1:10 (predatory mite/pest) was effective in controlling T. urticae too on strawberry too, both in the field and greenhouse, maintaining the pest mite population at low levels for long period [29].…”
Section: Total Number Of Oligonychus Ilicis Mobile Phasesmentioning
confidence: 99%